Alternative in the treatment of fibrocystic mastopathy with tamoxifen - Baquerizo Olaya,, Manuel; Bueno Suárez, Nelson; Parra Paredes, Nelly; Franco Tumbaco, Mirella (Revista Universidad de Guayaquil, 1994)
In the Mastology clinic of the "Teodoro Maldonado Carbo" Hospital of the IESS of Guayaquil, 50 patients between 18 and 53 years old, with Fibrocystic Mastopathy (MFQ) were studied from May/93 to April/94 who underwent surgery, at the beginning of the complete clinical history, physical examination, prolactinemia, breast ultrasonography and mammography for patients over 35 years of age. TAMOXIFEN was administered at a dose of 10 mg daily for four months, with clinical monitoring, prolactinemia and breast ultrasonography performed at 4 and 12 months.